Effect of Discontinuous Yielding on the Strain Hardening Behavior of Fine-Grained Twinning-Induced Plasticity Steel - Kang, Singon; Jeong, Sujin; Ahn, Yeon-Sang (Frontiers in Materials, 2021)
The yielding of a high Mn twinning-induced plasticity steel was examined in three fine-grained specimens recrystallized at 700°C for 5 min with different cooling conditions. While the stress-strain curves of furnace-cooled and air-cooled specimens exhibit a stress drop at yielding, the drop was not observed in the water-quenched specimen. A simple analysis of the displacement data indicates the occurrence of localized deformation at the beginning of the plastic deformation in the three tensile specimens with different cooling conditions. The localized deformation of all three specimens was confirmed as Lüders strain by digital image correlation (DIC) analysis. Based on this observation, the role of yielding behavior on the strain hardening rate evolution at an early stage of the tensile deformation was discussed.